Tinjauan Hukum Islam Terhadap Pembagian Harta Warisan Menurut Tradisi Masyarakat Karo (Studi Kasus di Desa Sanggalima) - Diki Attailah; Muhammad Saleh (Stigma Jurnal Ilmu Sosial Politik dan Humaniora, 2022)
The problem in this study is the distribution of inheritance in the customary law of the Karo people in Sanggalima Village, Gebang District where in the distribution of female inheritance, girls do not get inheritance if they are with boys, the reason is because the boys are more of a patrilineal system. . The purpose of this study was to find out the review of Islamic Law on the Tradition of the Implementation of the distribution of inheritance in the Karo Community tradition in Sanggalima Village, Gebang District. This type of research is empirical research with a case study approach. Methods of collecting data by means of observation, interviews, and literature study. The conclusion in this study is that among the Karo people in the distribution of inheritance in Sanggalima Village, Gebang District, it is a habit (urf) in using customs in the distribution of inheritance. And it has been carried out successively since ancient times or has been passed down from generation to generation, but it is contrary to the arguments of the Qur'an and Hadith which resulted in unacceptable customs in Sanggalima Village, namely regarding equal results between male and female heirs, as stated contained in the Qur'an letter An-nisa verse 11 states that part 2: 1. So that the method of dividing the inheritance of Sanggalima Village is not in accordance with the provisions in the Qur'an regarding Islamic inheritance law